2013
DOI: 10.1175/jcli-d-12-00259.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Temperature and Precipitation Trends and Long-Term Persistence in CMIP5 Twentieth-Century Climate Simulations

Abstract: The authors have analyzed twentieth-century temperature and precipitation trends and long-term persistence from 19 climate models participating in phase 5 of the Coupled Model Intercomparison Project (CMIP5). This study is focused on continental areas (60°S–60°N) during 1930–2004 to ensure higher reliability in the observations. A nonparametric trend detection method is employed, and long-term persistence is quantified using the Hurst coefficient, taken from the hydrology literature. The authors found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
173
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(199 citation statements)
references
References 28 publications
21
173
1
4
Order By: Relevance
“…Although the models are unable to simulate the observed pattern, the observed variability is simulated relatively well by the CCSM4 and the EM over the basin and the three belts. In the case of the EM, this study is consistent with previous studies (e.g., [19,20]) that suggest better performances for EMs.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Although the models are unable to simulate the observed pattern, the observed variability is simulated relatively well by the CCSM4 and the EM over the basin and the three belts. In the case of the EM, this study is consistent with previous studies (e.g., [19,20]) that suggest better performances for EMs.…”
supporting
confidence: 92%
“…ey also indicated the superior performance of the multimodel ensemble mean to the individual models. Kumar et al [20] have also evaluated temperature and precipitation trends in 19 CMIP5 GCMs, focusing on continental areas (60°S-60°N) for the period. ey showed that there are large uncertainties in the models in simulating local-scale temperature and precipitation trends.…”
Section: Introductionmentioning
confidence: 99%
“…CMIP5 models were chosen based on research by Kumar et al (2013) that evaluated the performance of 19 CMIP5 models in replicating historical data trends. Of the 19 models tested, CCSM4.0 had the highest correlation with historical precipitation trends, while GFDL and MIROC had the highest correlation with historical temperature trends (Kumar et al, 2013).…”
Section: Model Scenariosmentioning
confidence: 99%
“…Our ability to make accurate predictions about future climate, and in particular future precipitation, thus rests on our understanding of the tropical Pacific climate under different climate boundary conditions than today. Global climate models exhibit significant inter-model differences in their simulations of recent and future precipitation change over the IPWP (Kumar et al, 2013;Meehl et al, 2007), as do simulations of IPWP precipitation under glacial boundary conditions (DiNezio et al, 2011;DiNezio and Tierney, 2013), motivating scientific drilling at Lake Towuti.…”
Section: Introductionmentioning
confidence: 99%